PENGARUH PENAMBAHAN KARAGENAN TERHADAP KARAKTERISTIK FISIK DAN SENSORI MI BASAH SUBSTITUSI TEPUNG KEDELAI (Glycine max (L.) Merill) - -, Naomi Azzahra; Koesoemawardani, Dyah; Danar Tri Winanti, Diki; Nurainy, Fibra (Jurusan Teknologi Hasil Pertanian, 2025)
Food diversification using soy flour in made wet noodles has been carried out in Indonesia. However, the absence of gluten in soybeans can reduce the physical characteristics of the resulting wet noodles. Natural additives in the form of carrageenan are known to form thermoreversible elastic gels. This study aims to determine the effect of adding carrageenan on the characteristics of wet noodles substituted with soy flour and to determine the addition of carrageenan with the characteristics of the best wet noodles substituted with soy flour according to SNI 2987-2015. The study used a Completely Randomized Block Design (RAKL) with one factor with four replications. The factors used were carrageenan and glucomannan formulations with 6 treatment levels, namely P1 (0%), P2 (4%), P3 (8%), P4 (12%), P5 (16%), P6 (20%). Data were analyzed using the Barlett and Tukey test, followed by the ANOVA test and the honest significant difference (BNJ) test at the 5% level. The results showed that the addition of carrageenan affected the physical and sensory properties of wet noodles substituted with soy flour. The best wet noodle treatment was treatment P4 (12% carrageenan) with a water content of 70.08%, cooking loss of 1.53%, elongation of 17.50%, texture score (between chewy and slightly chewy), colour score (between light brown and light brown), and protein content of 23.1%.